Social Spaces of Music: Introduction. (March 2015) - Crossley, Nick; Bottero, Wendy
This paper introduces a special issue of Cultural Sociology focused upon 'music worlds', 'music scenes', 'music fields' and musically focused 'networks' – the expression in the title, 'social spaces of music', is intended as a neutral means of capturing the (shared) focus of these different concepts. The paper begins with a brief discussion of the various ways in which such spaces have been conceptualized through the history of sociology, affording specific attention to the concept of subculture, before introducing the four key concepts referred to above. Discussion then turns to a number of key ideas and themes which these conceptions share, before introducing the other papers in the special issue.